1975
DOI: 10.1017/s0376892900000631
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Zinc, and Manganese, in Dredge-spoil Pond Ecosystems

Abstract: Pb, Zn, and Mn, levels in sediment and common estuarine plants and animals colonizing dredge-spoil disposal areas were compared with levels occurring in the same materials from a natural salt-marsh. Finegrained dredge-spoil had considerabily higher levels of all three metals than did natural salt-marsh sediment, and large differences in the metals content of the spoil were observed, depending on sediment type.Pb levels in the Grass Shrimp (Palaemonetes pugio), Mummichog (Fundulus heteroclitus), Common Reed (Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1976
1976
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…This demonstrates that in considering the environmental consequences of metal uptake, conditions within the animal, in addition to detailed speciation studies of metals in the soils, grass or water, have to be taken into account. In a similar study, Pb and Mn also tended to decrease markedly with increasing trophic level in both detritus-based, and grazing food chains in a dredge spoil pond, but no consistent pattern was observed in the case of Zn (Drifmeyer & Odum, 1975). However, on several occasions in this study, higher consumers such as mating shore birds and migratory wildfowl were observed feeding in the spoil pond, and thus the dredge spoil may have been a source of certain heavy metals that are potentially toxic to higher trophic organisms; consideration of the problems should, therefore, not be confined solely to domestic animals.…”
Section: E N V I R O N M E N T a L A N D H E A L T H R I S K Smentioning
confidence: 83%
“…This demonstrates that in considering the environmental consequences of metal uptake, conditions within the animal, in addition to detailed speciation studies of metals in the soils, grass or water, have to be taken into account. In a similar study, Pb and Mn also tended to decrease markedly with increasing trophic level in both detritus-based, and grazing food chains in a dredge spoil pond, but no consistent pattern was observed in the case of Zn (Drifmeyer & Odum, 1975). However, on several occasions in this study, higher consumers such as mating shore birds and migratory wildfowl were observed feeding in the spoil pond, and thus the dredge spoil may have been a source of certain heavy metals that are potentially toxic to higher trophic organisms; consideration of the problems should, therefore, not be confined solely to domestic animals.…”
Section: E N V I R O N M E N T a L A N D H E A L T H R I S K Smentioning
confidence: 83%
“…Many investigators have reported that heavy metals are often closely associated with sediments and upper-soil horizons [22], [23], [24], [25]. Actual measurements of equilibrium uptakes in wetlands are difficult to obtain.…”
Section: H E a V Y Metalsmentioning
confidence: 99%
“…Les donn6es de la litt6rature r6sultant soit de mesures in situ de la concentration des m6taux en fonction du niveau trophique des organismes, soit d'exp6riences de contamination des organismes par voie alimentaire, confirment que s'il y a une bioaccumulation* non n6gligeable de Cd, Pb et Cu chez les organismes aquatiques, il n'y a vraisemblablement pas biomagnification" * dans les r6seaux alimentaires (Bohn & Mc Elroy, 1976;Aubert et al, 1972Aubert et al, , 1974Aubert et al, , 1975Aubert et al, , 1976Drifmeyer & Odum, 1975;Rehwoldt et al, 1978;Hodson et al, 1978;Steele et al, 1973).…”
Section: Evolution De La Concentration M~tallique Dans Les Aliments Aunclassified